New Financial Technologies: New Opportunities and New Challenges of the XXI Century (Journal of Economic Research & Business Administration, 2021)
Financial technology, or “Fintech”, is a sphere comprising from firms which are related to technology,and work in order to create a competitive environment for existing financial companies, and tocreate new services in the markets.Fintech is created in order to offer new convenient solutions in the financial environment. On theone hand, these innovations work and bring high profits to the creators. Fintech provides an opportunityfor renewed activity in underdeveloped markets that are less attractive to investors, especially in today’senvironment (for example, money transfers).On the other hand, such a drive motivates to create innovations in the financial markets. Organizationsbuilt on these models are now at the forefront of the modern technologies in finance. The actualreason of this article is to find and show the nature of the modern concept, trends, and challenges fornew financial technologies in Kazakhstan and abroad.The article discusses the financial technologies concepts and their impact on to the economy; analyzesthe main indicators of financial technology development in Kazakhstan mostly in the bankingsector. The article explores the theoretical and methodological foundations of modern Fintech processbased on the analysis of relevant works in this field of study. Issues of modern references, magazines,and Internet resources were used for the research.The theoretical and practical significance of this work determines a wider range of disclosure of thebasic conceptual apparatus and the search for modern ways to use the results in the activities of variousinstitutions for the development of measures to improve them.Key words: financial technologies, digital technologies, mobile wallets, P2P.